PSYCHOLOGICAL FEATURES OF PROFESSIONAL TRAINING OF TEACHER PSYCHOLOGISTS - Aziza E. Mukhtarova (American Journal Of Social Sciences And Humanity Research, 2022)
In the context of dynamic processes taking place in the economy of Uzbekistan, the current stage of development of society is characterized by a change in educational paradigms, a transition to new pedagogical technologies focused on variability, subjectivity, creative individuality, personal potential of specialists who are as ready as possible for practical activities, able to quickly engage in innovative processes and adjust their professional activities.